2022
DOI: 10.1029/2021jf006406
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Mapping of Subglacial Hydrology Reveals Previously Undetected Pressurization Event

Abstract:  Subglacial water flow generates continuous seismic tremor observable in the power spectra recorded by on-ice seismometers. Using a dense array of seismometers to detect glaciohydraulic tremor allows us to map subglacial pressurization in space and time. Seismic data indicate pressurization in the upper glacier, particularly near the margins, that was not perceptible in glacier velocity data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 53 publications
(114 reference statements)
1
6
0
Order By: Relevance
“…The main difference between the data from Greenland and the data from Gornergletscher is that in Figure 9 the low frequency window (i.e., 14-30 Hz) is consistently higher than the other two frequency windows. An explanation for this could be that the SG-box in Greenland was located close to a sub-glacial or englacial water channel or moulin that would dominate on-ice noise in this frequencies range (Bartholomaus et al, 2015;Röösli et al, 2016b;Köpfli et al, 2022;Labedz et al, 2022). The hydrological system on the Greenland icesheet is of a different scale than at an Alpine glacier, such as Gornergletscher.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The main difference between the data from Greenland and the data from Gornergletscher is that in Figure 9 the low frequency window (i.e., 14-30 Hz) is consistently higher than the other two frequency windows. An explanation for this could be that the SG-box in Greenland was located close to a sub-glacial or englacial water channel or moulin that would dominate on-ice noise in this frequencies range (Bartholomaus et al, 2015;Röösli et al, 2016b;Köpfli et al, 2022;Labedz et al, 2022). The hydrological system on the Greenland icesheet is of a different scale than at an Alpine glacier, such as Gornergletscher.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, seismic energy caused by glaciohydraulic processes and surface meltwater flow is concentrated at frequencies below 35 Hz (Bartholomaus et al, 2015;Podolskiy and Walter, 2016;Röösli et al, 2016b;Labedz et al, 2022) and is therefore not likely to explain the periods of high frequency noise (>100 Hz) during pe-riods with low wind speeds and high air temperature such as at the start and end of the test period. We also have to consider that the weather data originates from a weather station next to the Monte Rosa Hut, which is 850 m from the deployment and at 450 m higher elevation.…”
Section: Background Noise Wind and Air Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…Juretzek & Hadziioannou 2016), sediment transport in rivers (Tsai et al 2012), glacier hydrology and dynamics (e.g. Aso et al 2017;Labedz et al 2022), tropical cyclones (e.g. Retailleau & Gualtieri 2019) and underground hydrothermal activity (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Due the co-existence of different subglacial drainage system components and their dynamic evolution over time, the interpretation of the hydro-mechanical conditions variations from borehole studies solely remain very local and challenging to extrapolate at glacier-scale. Recent studies have shown the potential of using cryoseismology to bridge the gap between observations at different scales (Podolskiy and Walter, 2016), for instance by inferring hydraulic conditions across various temporal (sub-daily to multi-year) and spatial (decametric to kilometric) scales (Bartholomaus et al, 2015;Gimbert et al, 2016;Nanni et al, 2020;Lindner et al, 2020;Labedz et al, 2022). This is based on the principle that turbulent water flow generates seismic tremor at high frequency (>1 Hz) can be used to quantify relative changes in the subglacial drainage system conditions (Gimbert et al, 2016).…”
Section: Introductionmentioning
confidence: 99%